Association between cardiovascular risk factors and colorectal cancer: A systematic review and meta-analysis of prospective cohort studies - Zhang, Chen; Cheng, Yunjiu; Luo, Dongling; Wang, Jinghua; Liu, Jianhua; Luo, Yujun; Zhou, Weijie; Zhuo, Zewei; Guo, Kehang; Zeng, Ruijie; Yang, Jun; Sha, Weihong; et al. (EClinicalMedicine, 2021)
Emerging data have suggested colorectal cancer (CRC) often coexists with cardiovascular diseases, but whether cardiovascular risk factors play a role in CRC remains unclear. We performed a systematic review and meta-analysis to better illustrate the associations between cardiovascular risk factors and CRC. We searched EMBASE, MEDLINE and Web of Science databases from inception up to June 14, 2020. Prospective cohort studies were included if they evaluated the association between at least one of cardiovascular risk factors and CRC incidence, containing sufficient data to obtain relative risk (RR) and 95% confidence interval (CI). We performed separate meta-analyses for each cardiovascular risk factor using random-effect model. PROSPERO registration number: CRD42020175537. Data from 84 studies, reporting 52, 348, 827 individuals and 384, 973 incident cases were included in the analysis. Overall, the risk of CRC was 1.31(95% CI, 1.21–1.42) for obesity, 1.14 (95% CI, 1.09–1.20) for per 5 kg/m2 increase in body mass index, 1.18 (95% CI, 1.14–1.23) for former smoker, 1.20 (95% CI, 1.11–1.30) for current smoker, 1.25 (95% CI, 1.16–1.35) for diabetes, 1.07 (95% CI, 1.02–1.12) for hypertension. The summary RRs of CRC for the highest versus lowest quartiles of total cholesterol, triglyceride, low-density lipoprotein were 1.12 (95% CI, 1.03–1.22), 1.18 (95% CI, 1.04–1.35), 0.85 (95% CI, 0.62–1.17) respectively and the pooled RR for the lowest versus highest quartile of high-density lipoprotein was 1.14 (95% CI, 1.02–1.28). Unfavorable cardiovascular risk factors are associated with increased risk of CRC, which may provide novel insight into the screening strategies of CRC in patient with these risk factors.